Identifikasi Spesies Daging Secara Imunologi - Amhar Abubakar (Agricultural Faculty, 2001)
ABSTRACT To detect the meat or meat product adulterated in beef products, the research was carried out with using immunological tecnique (agar gel precipitation test). The purpose of this study was to investigate various antigen preparation, to determine the optimum method for producing antiserum of the desired titer and specificity, and to know whether antiserum from fresh meat still capable to determine extract from cooked meat. Six kinds of extract antigen from beef and 3 kinds of meat proteins were used in the research. Those were 6 kinds of extract antigen from fresh meat, wet dendeng, dry dendeng, frest bakso, cooked bakso and abon, and 3 kinds of meat protein from globulin, myoglobin and actomyosin. The rabbit were injected intramusculary and intravenausly on alternate weeks for eight injections and were tested every week to detect titers of antiserum. The results showed that intramuscular and intravenous injection of extract antigen from frest meat, frest bakso and cooked bakso emulsified in Freund Complete Adjuvant causad antibodies production higher titers thant wet dendeng and dry dendeng, whereas extract from abon showed a negative gel diffusion response after 8 weeks injection. Serum corresponding to the extract from the other cooked meat, except the extract from abon. The extract from abon always indicated a negative response on gel diffusion test. Injection of globulin and myioglobin showed a strong positive gel diffusion test after 8 weeks with extract from frest meat, whereas actomyosin resulted in negative response to extract from fresh meat by gel diffusion test.Key Word : Antigen; Antibody; Intravenous; Intramuscular and